Exploring leadership foundations and perspectives: relevant models, theories, and challenges - Castiblanco Romero, Johana Katherine; Ruiz Castro, Ivan Ricardo (Cuadernos de Administración, 2025)
Leadership, in a globalized world and in a changing organizational context, is a matter of high relevance today. In this sense, the present paper explores different theories and models of organizational leadership, identifying its historical, conceptual and methodological bases, as well as its practical implications in current organizational contexts. We begin with an approach to classical models of leadership, mainly focused on people’s characteristics associated with good leadership behaviors. We also explore, the leader-member exchange theory, which is the basis for the contemporary leadership theories. Contemporary models of leadership are also reviewed, incorporating contextual elements, as well as group characteristics as fundamental aspects for successful leadership. Finally, the current trends in organizational leadership are presented, which are oriented mainly to strategic leadership, the use of new technologies and digital transformation in its practice, as well as the develop of creativity, flexibility and the enhance of the approach of authentic leadership. It is also suggested how the study of leadership in the Colombian and latinoamerican context is oriented, emphasizing the relevance of authentic leadership and its advantages and contribution to organizational contexts.